2021
DOI: 10.1111/petr.14150
|View full text |Cite
|
Sign up to set email alerts
|

Age‐ and sex‐mediated differences in T lymphocyte populations of kidney transplant recipients

Abstract: Background: Graft failure rates increase through childhood and adolescence, decline in adulthood, and are higher in female than male kidney transplant recipients (KTR) until middle age. We aimed to describe age-and sex-related differences in T-cell subsets among KTR to determine which differences may help to explain the differences in kidney graft failure rates. Methods: Effector T (Teff)-cell and regulatory T (Treg)-cell phenotypes in PBMCsfrom healthy controls and KTR, who were at least 1 year post-transplan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 57 publications
0
3
0
Order By: Relevance
“…For example, the possibility that young females have a more potent immune response than young males should be considered. 40 The impact of cyclical sex hormones on the pharmacokinetics of immunosuppressive medications should also be investigated. Finally, the explanation for superior graft survival among older women than men should be sought.…”
Section: Discussionmentioning
confidence: 99%
“…For example, the possibility that young females have a more potent immune response than young males should be considered. 40 The impact of cyclical sex hormones on the pharmacokinetics of immunosuppressive medications should also be investigated. Finally, the explanation for superior graft survival among older women than men should be sought.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, Th17 levels in patients with CKD who have not undergone KT are also lower than those after KT, suggesting that immune response is the cause of the development of CKD after transplantation ( 45 , 51 ). Retrospective studies have found that the increase in the proportion of Th17 cells is consistent with the increase in the rate of graft failure ( 52 ). In addition, Th17 infiltration of allograft has a certain indicator effect on transplantation prognosis and anti-rejection response ( 53 ).…”
Section: Relationship Between Th17 Treg and Ktmentioning
confidence: 86%
“…A study of kidney transplantation among 3–29-years-old showed that Th1 (IFNγ + IL-4 − L-17A − ) and Th17 (IL-17A + ) frequencies within CD4 + T cells could be higher at older ages, but the frequencies of FOXP3 + Treg cells in CD4 + CD25 + CD127 − T cells were lower in females than in males ( 38 ). This report did not show serum estrogen levels; however, women in their twenties could be estimated to have higher estrogen levels than pre-adolescent and post-menopausal women.…”
Section: Effect Of Sex and Aging On Organ Transplantationmentioning
confidence: 99%